Adsorption of methane in organic-rich shale nanopores: An experimental and molecular simulation study. (15th July 2017) - Xiong, Jian; Liu, Xiangjun; Liang, Lixi; Zeng, Qun
Highlights: The proportion of adsorbed gas decreased as pressure increases under the same pore size and decreased as pore size increases under the same pressure. The methane was mainly in free state under higher pressure in different types of pores when the pore size was more than 6 nm. The methane adsorption capacity in different types of pores decreased in the following order: organic pore > clay minerals pore > quartz pore. The organic pores contributed more to the adsorbed gas while the quartz pores contributed more to the free gas. Abstract: In this article, the adsorption behaviors of methane on organic-rich shales were investigated through experimental and molecular simulation. The results showed that the methane adsorption capacity on kerogen is much greater than that of minerals and the methane adsorption capacity of clay minerals is greater than that on quartz. The isosteric heats of adsorption of methane decrease upon increasing the pore size or decreasing the O/C ratio. The volume proportion of adsorbed gas decreases as the pressure increases under the same pore size and declines as the pore size increases under the same pressure. The methane is mainly in the free state under high pressure in different types of pores of organic-rich shales when the pore size is greater than 6 nm. The organic pores contribute more to the adsorbed gas, whereas the quartz pores contribute more to the free gas. The methane adsorption capacity decreases in the following order: organic pore > clay mineral pore > quartz pore. The methane adsorption capacity in the micropores increases with the increasing pore size, whereas that in the mesopores decreases. The methane adsorption capacity under the same pore size decreases with the decreasing O/C ratio. There are differences in the methane adsorption capacity on clay minerals between the macroscopic level and microscopic level, which probably refers to the specific surface. With an increasing pressure or decreasing pore size, the adsorption sites of methane in different types of pores gradually change from higher-energy adsorption sites to lower ones, resulting in an increase in the methane adsorption capacity.